CNT and polyaniline based sensors for the detection of acid penetration in polymer composite. (3rd May 2018) - Liu, Chang; Sergeichev, Ivan; Akhatov, Iskander; Lafdi, Khalid
Abstract: Today, polymer composites are used to store liquid chemicals. Monitoring their structural health is crucial. In this study, conductive nanocomposite-based sensors were designed to monitor acid penetration over time. The sensors were made using blends of epoxy resin and additives, such as polyaniline and carbon nanotube (CNT). It appeared that as the concentration of additives increased, the sensors' response time were shorter. The CNT-based nanocomposites had shown an especially high sensitivity. However, to track the acid penetration over time, polyaniline-based sensors seem more adequate. A simple kinetic model was developed to have a better understanding of sensor behavior.